Construction Scheduling Optimization of Prefabricated Buildings Under Resource Constraints Based on an Improved Whale Optimization Algorithm - Rui Su; Joey S. Aviles (International Journal of Computational Intelligence Systems)
Abstract Prefabricated construction offers significant advantages in efficiency, resource savings, and environmental sustainability, yet its scheduling remains challenging due to complex resource constraints and task interdependencies. This study proposes a dual-objective optimization model to minimize project duration and resource fluctuation in prefabricated construction projects. To solve this model effectively, an Improved Whale Optimization Algorithm (IWOA) is developed, addressing the limitations of the standard WOA such as premature convergence and poor local search ability. The proposed IWOA incorporates Tent chaotic mapping for population diversification, a nonlinear convergence factor to balance exploration and exploitation, and a hybrid search mechanism that integrates crossover operations and multiple neighborhood strategies. A real-world case study demonstrates the algorithm’s superiority over conventional approaches in both solution accuracy and stability. The results show that the optimized schedule significantly improves resource allocation efficiency and reduces construction time, offering a promising approach for intelligent scheduling in resource-constrained prefabricated building projects.